Molecules from Side Reactions II - D'Errico, Stefano; Guaragna, Annalisa (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
"Molecules from Side Reactions II" is the second edition of the Special Issue "Molecules from Side Reactions". Both the Special Issues belong to the section "Organic Synthesis" of the journal Molbank (ISSN 1422-8599). "Molecules from Side Reactions II" showcases brief papers whose main topic is the synthesis and characterization of molecules obtained from unexpected and/or unpredictable synthetic routes. This Special Issue was revealed to be an important discussion forum for the dissemination of multidisciplinary research results.